Microscopic Origin of the Solid Electrolyte Interphase Formation in Fire-Extinguishing Electrolyte: Formation of Pure Inorganic Layer in High Salt Concentration - Bouibes, Amine; Takenaka, Norio; Saha, Soumen; Nagaoka, Masataka (The journal of physical chemistry letters, 2019)
A highly salt-concentrated (HC) electrolyte based on the nonflammable solvent trimethyl-phosphate (TMP) has recently shown an attractive self-extinguishing property in addition to an excellent charge-discharge performance. However, the microscopic understanding of its solid electrolyte interphase (SEI) layer remains an open question. In this Letter, the red moon (RM) method was used to investigate the molecular mechanism of SEI layer formation depending on lithium bis(fluorosulfonyl)amide (LiFSA) salt concentration in a TMP-based electrolyte and was able to reproduce successfully the experimental observations, i.e., the "bottom-up" formation mechanism with a thinner and denser SEI layer mainly based on salt reduction in the HC electrolyte. The results showed that a pure dense inorganic layer is formed in the HC electrolyte, which should considerably improve the SEI layer stability leading to a longer lifetime in charge-discharge performance. This new microscopic finding should provide an important guide in designing an effective nonflammable electrolyte to develop advanced, safe secondary batteries.A highly salt-concentrated (HC) electrolyte based on the nonflammable solvent trimethyl-phosphate (TMP) has recently shown an attractive self-extinguishing property in addition to an excellent charge-discharge performance. However, the microscopic understanding of its solid electrolyte interphase (SEI) layer remains an open question. In this Letter, the red moon (RM) method was used to investigate the molecular mechanism of SEI layer formation depending on lithium bis(fluorosulfonyl)amide (LiFSA) salt concentration in a TMP-based electrolyte and was able to reproduce successfully the experimental observations, i.e., the "bottom-up" formation mechanism with a thinner and denser SEI layer mainly based on salt reduction in the HC electrolyte. The results showed that a pure dense inorganic layer is formed in the HC electrolyte, which should considerably improve the SEI layer stability leading to a longer lifetime in charge-discharge performance. This new microscopic finding should provide an important guide in designing an effective nonflammable electrolyte to develop advanced, safe secondary batteries.